“Congenital Diaphragmatic Hernia – Treatment and Outcomes” - Pandya, Kashyap; Pancholi, Mukesh; Pandya, Ananyaa; Patel, Jagrutkumar (Journal of Neonatal Surgery, 2025)
Background:Congenital diaphragmatic hernia (CDH) is a rare but life-threatening developmental anomaly characterized by herniation of abdominal viscera into the thoracic cavity, leading to pulmonary hypoplasia and pulmonary hypertension. Despite major advances in neonatal intensive care and surgical techniques, CDH continues to pose significant diagnostic and therapeutic challenges, especially in resource-limited settings. Aim:To evaluate the clinical presentation, surgical management, postoperative complications, and survival outcomes of neonates and infants diagnosed with congenital diaphragmatic hernia. Methods:This observational study was carried out in the Department ofSurgery, S.S.G. Hospital, Vadodara, Gujarat, over a period of six years and three months (June 2019 – September 2025). A total of 50 neonates and infants with confirmed CDH were included. Data regarding demographic profile, antenatal findings, clinical presentation, imaging results, type of defect, associated anomalies, surgical approach, and postoperative outcomes were recorded and analyzed using SPSS version 26. Descriptive statistics and Chi-square test were applied, with p < 0.05 considered significant. Results:Among the 50 cases, 32 (64%) were males and 18 (36%) females, with a mean birth weight of 2.45 ± 0.38 kg. Bochdalek hernia was the most common type (88%), predominantly left-sided (76%). Antenatal diagnosis was achieved in 21 cases (42%), while 29 (58%) were diagnosed postnatally. Associated anomalies were found in 36%, mainly cardiac and intestinal defects. All patients underwent surgical repair—open subcostal in 100%, with mesh reinforcement in 14% for large defects. Postoperative complications occurred in 40%, including respiratory distress (18%), sepsis (10%), pneumothorax (6%), and recurrence (6%). The overall survival rate was 70%, with mortality primarily due to pulmonary hypertension (12%) and sepsis (10%). Antenatally detected and higher-birth-weight infants demonstrated better survival (p < 0.05). Conclusion:Congenital diaphragmatic hernia remains a critical neonatal emergency with high morbidity and mortality. Early antenatal detection, preoperative stabilization, and timely surgical intervention significantly improve survival. Strengthening neonatal intensive care facilities, managing pulmonary hypertension effectively, and ensuring multidisciplinary follow-up are essential for optimizing long-term outcomes in CDH survivors.